Budgeting in Oaxaca - Vammalle, Camila (OECD Publishing, 2017)
Oaxaca recently experienced a period of rapid growth of public expenditure, in response to social and economic priorities. These increases in expenditure were not accompanied with corresponding increases in actual revenues, thus leading to the build-up of deficits. In 2013, the state embraced a consolidation plan, increasing revenue collections and cutting public expenditure and investment, aiming to restore budgetary balance by 2016. The Secretariat of Finance of Oaxaca has recently introduced a more robust legal framework to ensure fiscal sustainability, and avoid such policy fluctuations in the future. Despite recent improvements, there is still space to improve budget practices towards a more planned, accountable, participative and transparent budget process, as well as having an institutional and legal framework in place to ensure these practices have continuity between administrations
Keywords: Finance and Investment; Governance